Sosialisasi dan Implementasi Pemanfaatan Spirulina Sebagai Bahan Kosmetik Alami dan Suplemen Kesehatan Bagi Masyarakat Kelurahan Caturharjo Pandak Bantul - Permadi, Adi; Maryudi, Maryudi; Nuraisyah, Fatma; Khakim, Mufti; Baswara, Ahmad Raditya Cahya; Aziz, Abdul; Hadi, Sofyan; Sinaga, Alexander Maruli Tua; Anugrah, Nawang; Ramadhan, Muhammad Kaisar Sutomo; Firdaus, Stradivary Maulida; Hakim, Muhammad Arif Lukman; Sofiana, Nurani (Civiliza Publishing, 2024)
The village of Caturharjo Pandak Bantul has had a tradition of using natural cosmetic ingredients in skin care and health, but the trend of the commercial cosmetics industry has shifted people's interest towards using natural ingredients. Public problems related to cosmetics include a lack of knowledge about cosmetic safety, beauty pressure, and the circulation of illegal cosmetic products. Community Service (PKM), which involves collaboration between the Caturharjo sub-district and the Ahmad Dahlan University community service team, aims to provide a solution by utilizing spirulina as a natural cosmetic ingredient and health supplement. Problem solving is carried out through educational activities, demonstrations on making and using facial cosmetics from spirulina, as well as monitoring and evaluation. The spirulina product used is the result of research funded by the Kedaireka Matching Fund in 2022 which has received BPOM permission and is considered suitable for consumption. This PKM also produces output in the form of a video recording which is published on the LPPM UAD YouTube channel and has Intellectual Property Rights (IPR) on the video. Through this outreach, it is hoped that the public can increase awareness in using cosmetics and understand the benefits of spirulina for health.